RASSF1A methylation, YAP1 activation and metastasis: a new role for an old foe in lung cancer - Oh, Min Hee; Lockwood, William W. (Journal of Thoracic Disease; Vol 9, No 5 (May 28, 2017): Journal of Thoracic Disease, 2017)
The majority of lung cancer patients die not from primary, but metastatic disease. While mutations/rearrangements in oncogenes such as KRAS, EGFR and ALK, occur early in tumorigenesis, experimental evidence suggests that additional alterations are required to promote tumor invasion and progression (1). Despite knowing a great deal about the molecular pathways associated with the metastatic phenotype, little is known about how these factors become deregulated to drive the spread of lung cancer cells.